Myeloid sarcoma of the rib: An atypical isolated chest finding - Antonio Raucci; Antonio Fontanarosa; Pasquale Somma; Carlo Bergaminelli; Tullio Valente; Gaetano Rea (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Myeloid sarcoma is a rare extramedullary myeloid tumor typically occurring in association with acute myeloid leukemia. We report an atypical case of myeloid sarcoma arising from the rib of a healthy young man with no specific blood test abnormalities. Once the malignant nature of the tumor was confirmed, a complete surgical excision was performed and definitive diagnosis was achieved by way of an exhaustive histopathological examination of surgical specimens. Systemic treatment was administered and currently neither systemic nor local relapse has been identified. Our experience suggests surgical resection could be a valid treatment in isolated myeloid sarcoma patients.